Robert Harris interviewed by Donna Fraser in the Australia 1938 oral history project - Harris, Robert, 1909-; Fraser, Donna; Australia 1788-1988: A Bicentennial History; Australia 1938 Oral History Project (1981)
Harris speaks of his home and living conditions with wife in his parent's home in 1938; local area of Broadmedow; lifestyle; recreation; family life and roles; family occupation; healthcare; religion; attitudes to Aborigines; migrants; schooling; employment experiences and conditions; experiences during the Depression; sex in the 1930s; Australia in the 1930s; overseas countries; social life.
Transcript unavailable, questionaire and answers (24 p.)
Recorded by the Australia 1938 Oral History Project as research for the book Australians 1938 from the series Australians, a historical library.
Digital master available
Timed summary (3 p.).
Keywords: Harris, Robert, -- 1909- -- Interviews; Families -- New South Wales -- Newcastle; Newcastle (N.S.W.) -- Social conditions